Arts education as a strategy for eradicating violent behavior among university students: A novel proposition - Javed Hassaan Chandio; Irshad Hussain; Hafiz Muhammad Ather Khan; Noshaba Gulrez (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
Globally we are living in difficult times when peace and human security have become big challenges that could have negative implications if not addressed properly. University students -the future leaders are also the victims of such threats and some of them involve themselves in violence by exerting violent behaviors. Therefore, it is the prime responsibility of universities to address these issues properly. The universities may take several measures to eliminate violence and promote socially accepted behaviors among students. However, amongst others, art education seems a novel and feasible strategy for eradicating violent behavior from amongst students. This article reviews different studies and art projects, their effects and benefits to articulate implications in tertiary education.
Keywords: 330; arts education; violent behavior; tertiary education; creativity; psychological harm; progressive mindset; self-expression